Research Performance and the Organizational Effectiveness of UK Universities - Richard Croucher; Paul Gooderham; Marian Rizov (Journal of Organisational Effectiveness: People and Performance, 2018)
We test Shattock's legacy reputation thesis that non-leading universities in the UK face insuperable resource barriers to entering the leading group. Employing regression analysis, we examine whether prioritizing research performance is a viable strategy for non-leading UK universities aiming to improve their organizational effectiveness. The dependent variable, organizational effectiveness, is measured by the annual Guardian rankings of universities. The main independent variable, research performance, is measured using “research power” (`RP'). RP is derived from the UK Research Excellence Framework (REF). For 2008-14 we find that changes in research performance impacted university rankings. However, we also find that changes to the rankings are largely confined to non-leading universities and have not led to these institutions breaking into the group of leading universities. Therefore, Shattock's thesis is supported.
Keywords: M11; M14; L30; 330; organizational effectiveness; research performance; UK universities